Three-dimensional thermomechanical analysis of epidermal electronic devices on human skin. (1st August 2019) - Zhang, Jianpeng; Li, Yuhang; Xing, Yufeng; Song, Jizhou
Highlights: A 3D analytical thermomechanical model is established for the EED/skin system. The temperature and thermal stress are given analytically. The interactions among multiple EEDs are studied. Abstract: Epidermal electronic devices (EEDs) that are ultrathin and ultrasoft can provide intimate contact to the skin and show great promise in human health monitoring. For the EED/skin system, knowledge on the thermomechanical coupling between EEDs and skin is critical since unexpected heating-induced discomfort may occur even for a few degrees of temperature increase when EEDs are in service. In this paper, a three-dimensional analytical model is established to investigate thermomechanical behaviors of EEDs with rectangular heating components on the skin based on the transfer matrix method by accounting for the Fourier heat conduction in EEDs and the bio-heat transfer in skin. The transfer equation for each layer of the system is derived analytically. The analytical predictions of the temperature increase and the maximum principal stress (abs) (i.e., the principal stress with the maximum absolute value) agree well with finite element analysis. The interactions among multiple heating components in EEDs are also investigated. These results may serve as the basis for thermomechanical analysis of the EED/skin system to minimize the adverse thermal effects to avoid human discomfort.